Time trends in incidence and severity of injury among collegiate soccer players in the United States. NCAA injury surveillance system, 1990-1996 and 2004-2009 - Chandran, A.; Barron, M. J.; Westerman, B. J.; DiPietro, L. (The American Journal of Sports Medicine, 2016)
Background: A number of sociocultural and environmental changes have occurred over the past several decades that may affect the risk of injury among young athletes playing soccer. Purpose: To identify trends in injury incidence and severity between 2 time periods (1990-1996 and 2004-2009) in both male and female National Collegiate Athletic Association (NCAA) soccer players in the United States. Design: Descriptive epidemiology study. Methods: Data were analyzed from the NCAA Injury Surveillance System. The rate ratio (RR), along with the 95% Wald CI, compared incidence density in 2004-2009 relative to that in 1990-1996. Results: Overall sex-pooled injury rates were significantly lower in the 2004-2009 cohort compared with the 1990-1996 cohort (RR = 0.88; 95% CI = 0.86-0.91), and this was true for almost every category of injury studied. We observed only 1 significant sex difference between the time periods with regard to noncontact injuries, as men experienced a significant increase in rate of noncontact injuries between 1990-1996 and 2004-2009 (RR = 1.09; 95% CI = 1.02-1.17), whereas women experienced a significant decrease (RR = 0.70; 95% CI = 0.67-0.75). Conclusion: These surveillance data show decreasing trends in collegiate soccer injuries. Whether these decreases are attributable to greater resources being allocated toward athlete health, injury management, or the safety of the playing environment cannot be determined. Given the prominence of soccer play in the United States, public health efforts should promote the use of this surveillance system to better inform and evaluate injury prevention practices and policies directed toward player safety.